2015
DOI: 10.1517/14656566.2015.1020791
|View full text |Cite
|
Sign up to set email alerts
|

Advances in pharmacotherapy for treating female sexual dysfunction

Abstract: We are still waiting for an approved pharmacotherapy for FSD. This is not the result of gender inequality in sexual medicine, but it reflects the need of balancing benefits and risks in order to provide effective and safe treatments to women of any age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 145 publications
0
34
0
4
Order By: Relevance
“…Topical oestrogen is recommended for dryness. Pharmaceutical treatment is an ongoing field of research [23,31].…”
Section: Discussionmentioning
confidence: 99%
“…Topical oestrogen is recommended for dryness. Pharmaceutical treatment is an ongoing field of research [23,31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that HCPs tend not to take a proactive approach to sexual health management in the middle and later life age groups, mainly because of inadequate training, constraints of time, personal attitudes, and beliefs that sex is not a priority for older women [27,28]. The expert panel strongly recommends HCPs to proactively raise the subject of VVA in their medical practice in order to encourage postmenopausal women to overcome their “taboos” and openly discuss urogenital symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…As there are no Food and Drug Administration (FDA) approved drugs for the enhancement of female sexual response, the use of drugs in laboratory studies has primarily focused on the feasibility of improving sexual functioning in clinical samples rather than using drugs as a means of inducing a sexual response in healthy volunteers. A number of vasoactive agents (e.g., [69–74]), neurotransmitter‐acting agents (e.g., [59,75]), and hormonal therapies (e.g., [76], see [77] for review) have been examined for their clinical utility in improving sexual response in clinical samples of women, and although many have produced increases in genital responding the lack of FDA approval has limited the applicability of these agents as a means of eliciting sexual response in laboratory studies.…”
Section: Methodsmentioning
confidence: 99%